Habitat suitability of Javan langur (Trachypithecus auratus) in Gunung Babakan, West Java, Indonesia - AHMAD FAUZI; ICHSAN SUWANDHI; YOYO SUHAYA (Society for Indonesian Biodiversity, 2025)
Abstract. Fauzi A, Suwandhi I, Suhaya Y. 2025. Habitat suitability of Javan langur (Trachypithecus auratus) in Gunung Babakan, West Java, Indonesia. Biodiversitas 26: 3815-3826. The Forest Management Unit (FMU) Ciamis is one of the forest management areas owned by Perum Perhutani, which has the predicate of High Conservation Value Forest (HCVF). One of the categories of HCVF was HCV 3, which encompassed areas with rare or endangered ecosystems. The endangered animal species found in the Gunung Babakan of FMU Ciamis is the Javan langur (Trachypithecus auratus). This study aimed to analyze the suitability of Gunung Babakan as a habitat for the Javan langur, assessing the feasibility of secondary forest conditions as an area of high conservation value, using a deductive research approach. The methods used were vegetation analysis with purposive sampling, Canopy Height Model (CHM), and Habitat Suitability Index (HSI) model based on research conducted by Maulahila et al. (2023) with several adjustments. In addition, the validation was conducted on the HSI model, using a Receiver Operating Characteristic (ROC) curve. The study results showed there were 66 plant species, 33 were feeding trees for Javan langurs, and 13 of them were the main food source. Moreover, the canopy conditions in the Gunung Babakan secondary forest were dominated by stratum C (4-20 m; 84% of the area), followed by stratum B (20-30 m; 14% of the area). Based on the results of the habitat suitability index scoring, Gunung Babakan Secondary Forest had a score ranging from 0.55 to 0.85, which was categorized as 'high' (0.55-0.75; 59% of the area) and 'excellent’ (0.76-0.85; 41% of the area). Furthermore, the results showed the HSI of the Javan langur had a moderate model accuracy level with an AUC value of 0.742. Overall, based on feeding vegetation, canopy height, and the HSI model, the area was suitable as a habitat for Javan langurs with several conservation measures.